Combined Flow Abstraction and Climate Change Impacts on an Aggrading Alpine River. Issue 1 (17th January 2018) - Bakker, M.; Costa, A.; Silva, T. A.; Stutenbecker, L.; Girardclos, S.; Loizeau, J.‐L.; Molnar, P.; Schlunegger, F.; Lane, S. N.
Abstract: Recent climatic warming and associated glacial retreat may have a large impact on sediment release and transfer in Alpine river basins. Concurrently, the sediment transport capacity of many European Alpine streams is affected by hydropower exploitation, notably where flow is abstracted but the sediment supply downstream is maintained. Here, we investigate the combined effects of climate change and flow abstraction on morphodynamics and sediment transfer in the Borgne River, Switzerland. From photogrammetrically derived historical Digital Elevation Models (DEMs), we find considerable net aggradation of the braided river bed (up to 5 m) since the onset of flow abstraction in 1963. Reaches responded through bed level steepening which was strongest in the upper most reach. Widespread aggradation however did not commence until the onset of glacier retreat in the late 1980s and the dry and warm years of the early 1990s. Upstream flow intake data shows that this aggradation coincided with an increase in sediment supply, although aggradation accounts for no more than 25% of supplied material. The remainder was transferred through the studied reaches. Estimations of bed load transport capacity indicate that flow abstraction reduces transport capacity by 1–2 orders of magnitude. While residual transport rates vary with morphological evolution, they are in the same order of magnitude as the sediment supply rates, which is why significant transport remains. However, the reduction in transport capacity makes the system more sensitive to short‐term (annual) changes in climate‐driven hydrological variability and climate‐induced changes in intake management and sediment delivery rates. Key Points: Hydropower‐related flow abstraction may drastically reduce sediment transport capacity, but only to rates that are of similar magnitude as sediment supply This causes downstream river bed aggradation and morphodynamics to be very sensitive to external forcing mechanisms related to flow management or climate change Climate‐driven sediment supply may propagate through Alpine streams despite large‐scale flow abstraction